PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA TAPAK TUAN. - Yani Lapian Siregar (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
Problems in this research are: How does the influence of competence on the performance of employees of the Tread Tuan Tax Service Office, how does the influence of motivation on employee performance, how does the influence of work discipline on employee performance, how does the influence of organizational commitment on employee performance, how does the influence of competence, motivation, work discipline and organizational commitment to the performance of employees of the Tread Tuan Primary Tax Service Office.The hypothesis proposed is: Competence has a positive and significant effect on the performance of the Tread Tuan Tax Office employee. Motivation has positive and significant effect on employee performance. Work discipline has positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance, competence, motivation, work discipline and organizational commitment has positive and significant effect on employee performance. Sir